Hegemoni Pluralitas Hukum Terhadap UU No. 01 Tahun 1974 (Studi Supremasi dan Legalitas Hukum Perkawinan di Indonesia) - Mohsi (MAHAKIM Journal of Islamic Family Law, 2021)
Legal plurality is an indisputable part of the concept of Indonesian statehood, including the construction of marriage law. The pluralism of marriage law in Law No. 01 of 1974 is proof that the marriage law adhered to in the Indonesian legal system still refers to the pluralism and diversity system. This research will examine the plurality of marriage law from the legality aspect which has implications for its legal status, between imperative and facultative. This study uses a statute approach with an emphasis on the concept of law and legal legislation. This research concludes that the plurality of kwainan law in Law Number 01 of 1974 is a necessity in a multicultural country, because the existence of this law aims to accommodate and integrate existing laws on this Bhineka earth.